IMPLEMENTASI RULE-BASED CHATBOT DAN FUZZY STRING MATCHING DALAM SISTEM INFORMASI LAYANAN HAJI DAN UMRAH DI PT ALFATA WAFIQAH WISATA - Nafi Beckhamsyah Siahaan; Muhamad Alda (LPPM Universitas Abdurrab, 2025)
The development of digital technology has driven various sectors to improve efficiency and competitiveness, including the tourism industry. PT Alfata Wafiqah Wisata, a company engaged in the tour and travel sector, still applies a semi-manual system for registration and information services, which involves filling out physical forms and manually transferring the data to Microsoft Excel. This approach poses risks such as data entry errors, difficulties in data management, and delays in responding to common inquiries – especially outside of working hours. This research aims to address these issues by developing a web-based information system for serving prospective Hajj and Umrah pilgrims. The system is equipped with a rule-based chatbot to provide information and manage data related to registration and payments. The system development follows the waterfall methodology and incorporates Fuzzy String Matching to handle typing errors when users input keywords. The result of this research is a web-based information system that assists PT Alfata Wafiqah Wisata in managing pilgrim data and providing fast, automated responses to frequently asked questions – even outside operational hours.